Webinar Series Pembelajaran Abad 21 bagi Guru MGMP IPS dan PPKn di KBB - Arnie Fajar; Khaerul Syobar; Sustin Komariah (Jurnal Nirta : Inovasi Multidisiplin, 2024)
Learning in the 21st century demands a change in the educational paradigm, especially in Social Science Education (PIPS) and Pancasila and Citizenship Education (PPKn). The challenges of globalization, technological developments, and the need for 21st-century skills, such as critical thinking, creativity, communication, and collaboration (4C), are the main factors in the transformation of learning. This article discusses innovative learning strategies in PIPS-PPKn, including a project-based approach, the use of digital technology, and strengthening national values ​​and student character. Through a literature review and analysis of best practices, this study highlights how the integration of technology and active learning methods can improve learning effectiveness and shape critical and character-based citizens.